A Gastrointestinal Toxicity during Low-Dose Methotrexate Treatment in Two Pediatric Patients with Acute Lymphoblastic Leukemia - Kotnik, Barbara Faganel; Prelog, Tomaz; Kavcic, Marko; Avcin, Simona Lucija; Jazbec, Janez; Kitanovski, Lidija; Dolzan, Vita (Archives of Clinical and Medical Case Reports, 2022)
Low-dose Methotrexate (LD-MTX) and 6-mercaptopurine (6-MP) are used in the maintenance phase of treatment of childhood acute lymphoblastic leukaemia. It was reported that individuals with reduced activity of two of the enzymes involved in the pathway of purine metabolism, thiopurine S-methyltransferase (TPMT) and nudix hydrolase 15 (NUDT15), will be exposed to higher levels of active metabolites and will be at higher risk of side effects, such as myelosupression. Therefore, dosing recommendations for 6-MP based on TPMT and NUDT15 genotype have been approved by FDA and have been published by the Clinical Pharmacogenetics Implementation Consortium and the Ditch Working Group. Though several studies were conducted on the toxicity of LD and HD-MTX in childhood ALL patients, none of the genetic markers so far have been used in MTX therapy protocols due to the lack of a clear association with the response and/or toxicity. We describe two pediatric patients who suffered from gastrointestinal toxicity following peroral administration of LD-MTX during maintenance therapy of ALL that diminished after switching to parenteral administration of the drug.